Repurposing ProTAME for Bladder Cancer: A Combined Therapeutic Approach Targeting Cell Migration and MMP Regulation - Ihsan Nalkiran; Hatice Sevim Nalkiran (Biology)
Bladder cancer, the fourth most common cancer type among men, remains a therapeutic challenge due to its heterogeneity and frequent development of chemoresistance. Cisplatin-based chemotherapy, often combined with gemcitabine, is the standard treatment, yet resistance and off-target effects in non-cancerous tissues limit its efficacy. This study evaluated the effects of cisplatin, gemcitabine, and the APC/C inhibitor proTAME, both individually and in combination, on cell migration and MMP2/MMP9 expression in RT4 bladder cancer and ARPE-19 normal epithelial cells. Molecular docking analyses were conducted to investigate the interactions of these compounds with MMP2 and MMP9. IC20 values for gemcitabine, cisplatin, and proTAME were applied in scratch-wound healing and quantitative real-time PCR (qRT-PCR) assays. Docking results predicted that proTAME may interact favorably with MMP2 (−9.2 kcal/mol) and MMP9 (−8.7 kcal/mol), showing high computational binding affinities and potential key hydrogen bonds; however, these interactions require further experimental validation. Scratch-wound healing and qRT-PCR assays demonstrated that proTAME-containing combinations were associated with reduced cell migration and decreased MMP2 and MMP9 expression in RT4 cells. Cisplatin combined with proTAME showed the most pronounced reduction in MMP expression and cell migration, with proTAME alone also exhibiting notable inhibitory effects. In ARPE-19 cells, gemcitabine and cisplatin upregulated MMP2 and MMP9 expression, suggesting a potential stress response, whereas proTAME mitigated this effect. These differential effects show the importance of tumor-specific responses in RT4 cells, where proTAME shows promise in enhancing the efficacy of chemotherapy by modulating MMP-related pathways involved in tumor migration and invasion. In conclusion, this study highlights the potential of proTAME as a repurposed agent in bladder cancer treatment due to its association with reduced cell migration and MMP downregulation. While these in vitro and in silico findings suggest a promising role for proTAME in combination therapies, further validation in advanced preclinical models is necessary to assess its therapeutic applicability and safety.